Supporting older eyewitnesses' episodic memory: the self-administered interview and sketch reinstatement of context. Issue 6 (2nd July 2020) - Dando, Coral J.; Gabbert, Fiona; Hope, Lorraine
ABSTRACT: Environmental support at retrieval improves episodic performance, yet there exists very few empirically evaluated techniques for supporting older witnesses/victims' remembering (>65 years). We investigated two techniques for use in a criminal justice context – the Self-Administered Interview and Sketch Reinstatement of Context. Older adults ( N = 134) witnessed an unexpected live event, following which half immediately completed a Self-Administered Interview and half did not (Time 1). All were interviewed 48 h later (Time 2) using one of three face-to-face interview techniques: Sketch Reinstatement of Context, Mental Reinstatement of Context, or no support Control. Those who completed a Self-Administered Interview at Time 1 recalled more correct information at Time 2 irrespective of interview condition and confabulated less. Likewise, participants interviewed using the Sketch Reinstatement of Context technique recalled more correct information and confabulated less, whether they had completed a Self-Administered Interview, or not. However, the Self-Administered Interview + Sketch Reinstatement of Context was the most effective combination, indicating an interaction between stabilising a memory trace quickly and how sketching appears to scaffold memory retrieval during face-to-face interviews.